A discrete method and experimental study for the propagation of shock wave induced by high-speed projectile entering water-filled tanks. (15th March 2022) - Chen, Tuo; Guo, Zitao; Zhao, Geng; Zhang, Wei
Abstract: To provide a general view of how the shock waves propagate and multi-reflect in a water-filled tank, a discrete method for the propagation of shock waves produced by high-speed projectile water entry was proposed based on the law of reflection in this present study. This method was employed to analyze the composition of shock wave fronts at typical moments, the reflection history of any point on the reflected wave front, and the reflection history of points on the arc of a continuous reflected wave front without inflection. Meanwhile, a shadowgraph visualization system for shock waves induced by high-speed projectile water entry was designed and used to capture the shock wave front propagation in the water-filled tank. So that, the images and the wave fronts obtained by the discrete method were combined to analyze the propagation characteristics of the shock wave produced by projectile water entry. Good agreements were found between the theoretical predictions and experimental results. Highlights: A discrete method for shock wave propagation in a water-filled tank was proposed. The composition and reflection history of shock wave fronts were analyzed. A shadowgraph visualization system for shock waves was designed. Good agreements were found between the theoretical and experimental results.